Soil acidification as an additional driver to organic carbon accumulation in major Chinese croplands - Zhang, Xinmu; Guo, Jingheng; Vogt, Rolf David; Mulder, Jan; Wang, Yajing; Qian, Cheng; Wang, Jingguo; Zhang, Xiaoshan (Geoderma, 2020)
•Impacts of N-induced soil acidification on SOC stock are assessed.•N fertilization synchronously causes soil acidification and SOC accrual.•Soil acidification increases SOC content by decreasing its decomposition.•Soil acidification is a linkage between N fertilization and SOC accumulation. Significant increase in soil organic carbon (SOC) has been found in Chinese croplands. Current literature largely attributes this to the increased organic C inputs from manure, crop straw and root. However, using a meta-analysis of 185 long-term trials and 6669 spatial data pairs across China, we show here that soil acidification is an additional significant cause for the SOC accumulation. Results from long-term experiments showed that soil acidification due to excessive N fertilization coincided with, and significantly (p < 0.01) contributed to, the observed SOC accrual. Spatially, the amount of SOC increase caused by soil acidification decreased with increasing initial content. In addition, the soil’s basal respiration rate (SBRR), microbial metabolic quotient (MMQ) and the percentage of dissolved organic carbon (DOC) relative to total SOC decreased significantly (p < 0.01) with soil pH decline. This indicates that soil acidification depresses the decomposition of organic matter, both by decreasing microbial activity and by increasing protection of SOC by mineral phases. Thus, N-induced soil acidification promotes the SOC accumulation in Chinese croplands, by increasing its stability. In contrast to the current view emphasizing the importance of organic C inputs, our meta-analysis reveals an alternative mechanism connecting N-fertilization and the resulting SOC accumulation in agricultural ecosystems. More research is needed to further clarify its operating processes, relative importance, and agro-environmental consequences.